Arabs and Others in Early Islam - Bashear, Suliman (SLAEI - Studies in Late Antiquity and Early Islam Ser., 2020)
This work investigates available early Arabic ad th and exegetical literature in order to determine the great complexity of how Arabs, Muslims and Arab-Muslims viewed themselves and members of other communities In particular, it focuses on the relation between definitions of ""Arabness"" and ""otherness"" with Islamic ascriptions of believers and nonbelievers and endeavors to trace the changing of these views over time. Moreover, this is an in-depth analysis of a series of ad ths and isn ds that discusses when, where, why, and by whom traditions were circulated during the 8th and 9th centuries.